FAKTOR-FAKTOR YANG MEMPENGARUHI KEPATUHAN WAJIB PAJAK BUMI DAN BANGUNAN DI KECAMATAN TELUK SEGARA KOTA BENGKULU - Yennita Asriyani; Karona Cahya Susena (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2016)
Land and building tax was one of taxes which was potentially to be explored as revenue source. Tax revenue was really determined from taxpayers obedience in running their responsibility in tax field. This researchwas aimed at explaining the effect of income rate, taxpayer knowledge, Service Quality, Taxpayers Awareness, and Tax Punishment in influencing tax payers obedience in paying rural and urbam land and building tax. The study was located at Teluk Segars district in Bengkulu city. The method used in this research was quantitative research, by using questionnaire as the instrument which was spread out to 91 rural and urban land and building tax, tax payers at Teluk Segara district. Data  analyzing in this study used rating scale and likert scale analysis. The result of this research showed that one of indicators, namely taxpayers knowledge, gained the highest score is 367 . It meant that the indicator could influence taxpayers obedience, but it was not the factor that was able to make taxpayers obedient to pay land and building tax because of private interest reason. The indicator which gained the lowest score is 171 was income rate which meant it could not influence taxpayers obedience because land and building tax rate was relatively cheap and achievable by them to pay.  Key Words: Income Rate, Taxpayer Knowledge, Service Quality, Taxpayer Awareness, Tax Punishment , Taxpayer Compliance